KINDS OF QUESTIONS MAKING EFL STUDENTS LEARN: STUDENTS’ PERCEPTION - Mushoffan Prasetianto (JOALL (Journal of Applied Linguistics and Literature), 2019)
Interactions in the classroom play an important role because learning occurs in the interactions between more knowledgeable person and less knowledgeable person. Interactions in the EFL classroom can be seen as a dialogic activity in which the lecturer raises questions to the students. This study attempted to uncover the types of questions which can make students learn. The participants of the study were the lecturer and students of Language Learning Assessment course. The data of this study were the students’ perceptions on what kinds of questions make them learn and lecturer’s verbal questions. The results of the study show that there are four kinds of questions raised by the lecturer, namely analogy, optional, convergent and divergent questions. From those kinds of questions, divergent questions can make students learn because those questions drive students to have a discussion in which students can interact each other.